Periodontal Regenerative Treatment of Intrabony Defects Associated with Palatal Grooves: A Report of Two Cases. (3rd June 2019) - Corbella, Stefano; Alberti, Alice; Zotti, Beatrice; Francetti, Luca
Abstract : A palatal radicular groove (PRG) is a morphological deformity, occurring during tooth development. It is usually located on the palatal aspect of maxillary incisors and frequently associated with periodontal or endodontic-periodontal lesions. Some treatment options were described for such lesions, including primary endodontic treatment and periodontal surgery and extraction with intentional replantation after removal of a PRG and endodontic treatment. The present paper reported two cases of PRG-associated deep intrabony defects, successfully treated with periodontal surgery with enamel matrix derivative (EMD) application and mechanical removal of PRGs, avoiding endodontic treatment or retreatment. The complexity of the diagnostic process was also discussed.